Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1021/acscatal.9b03599
|View full text |Cite
|
Sign up to set email alerts
|

“Inverting” X-ray Absorption Spectra of Catalysts by Machine Learning in Search for Activity Descriptors

Abstract: The rapid growth of methods emerging in the past decade for synthesis of “designer” catalystsranging from the size and shape-selected nanoparticles to mass-selected clusters, to precisely engineered bimetallic surfaces, to single site and pair site catalystshas opened opportunities for tailoring the catalyst structure for the desired activity and selectivity. It has also sharpened the need for developing approaches to the operando characterization, ones that identify the catalytic active sites and follow the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
159
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 137 publications
(161 citation statements)
references
References 200 publications
1
159
1
Order By: Relevance
“…Finally, an application of ML models that has received far less attention in other reviews is their potential to enhance experimental characterization. The interpretation and labeling of experimental images (e.g., scanning transmission electron microscopy (STEM)) and spectra (e.g., X‐ray diffraction (XRD), X‐ray absorption near‐edge structure (XANES), nuclear magnetic resonance (NMR), etc.) are today still mostly painstakingly carried out by humans.…”
Section: Applicationmentioning
confidence: 99%
“…Finally, an application of ML models that has received far less attention in other reviews is their potential to enhance experimental characterization. The interpretation and labeling of experimental images (e.g., scanning transmission electron microscopy (STEM)) and spectra (e.g., X‐ray diffraction (XRD), X‐ray absorption near‐edge structure (XANES), nuclear magnetic resonance (NMR), etc.) are today still mostly painstakingly carried out by humans.…”
Section: Applicationmentioning
confidence: 99%
“…[30][31][32][33][34][35][36][37][38][39] To address this problem, we have recently proposed a machine learning-based approach for the interpretation of experimental XAS data, where we employed articial neural networks (NNs) to extract the structural information. [40][41][42][43][44] In the case of EXAFS data interpretation, by exposing NN to thousands of training examples (theoretical EXAFS spectra, for which the corresponding structure was known) we could establish a relationship between spectral features and structure descriptors. The trained NN can then be used to directly invert experimental data, and quickly and accurately extract relevant structural information, such as partial radial distribution functions (RDFs).…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that the catalytic selectivity of this system can be tuned by varying the copper to zinc ratio, and that signicant structural changes take place under reaction conditions. 13,47 Here we take advantage of the sensitivity of our NN-EXAFS method 44 to monitor subtle chemical and structural changes taking place during the CO 2 RR as a function of the Cu-Zn NP composition and time. In particular, we will show that the reduction of copper and zinc species takes place on different time-scales, and that gradual alloying and a transition from a close-packed to a more disordered structure take place.…”
Section: Introductionmentioning
confidence: 99%
“…While the data are highly convoluted, a machine learning model's exceptional flexibility could enable atomistic-level characterization of the surface. There has been some exciting progress in this direction, [242][243][244] and is expected to significantly expand the power of spectroscopy.…”
Section: Autonomous Laboratory and Inverse Designmentioning
confidence: 99%